Arthroscopic capsular suture benefits the clinical prognosis of distal radius fracture with DRUJ instability - Peilong Jiang; Huajun Jiang; Feng Han; Sida Liu; Wei Qu (BMC Surgery)
Abstract Background This study investigated the effectiveness of capsular suture repair for triangular fibrocartilage complex (TFCC) in restoring distal radioulnar joint (DRUJ) stability after plate fixation for distal radius fracture (DRF) combined with acute DRUJ instability, comparing the results of arthroscopic capsular suture with those of conservative treatment of TFCC injury. Methods Cases of DRF combined with DRUJ instability treated from January 2019 to December 2022 were reviewed retrospectively. After plate fixation of the distal radius fracture, patients with acute DRUJ instability were divided into two groups. In the TFCC repair group, TFCC tears were repaired by arthroscopic capsular suture. In the TFCC conservative group, a cast and brace were applied for 6 weeks postoperatively. The MMWS score, PREW score, DASH score, VAS score, and grip strength were compared between the two groups over a minimum 12-month follow-up. This study included 55 patients in the repair group and 53 patients in the conservative group. In addition, the risk factors for chronic DRUJ instability after conservative treatment were investigated by univariate and multivariate regression analysis. Results The mean follow-up period thereafter was 15.2 months. All patients in the repair group showed DRUJ stability, whereas 15 of 53 patients (28.30%) in the conservative group showed DRUJ instability. The repair group also had a significantly better VAS score (P 1  < 0.001), PREW score (P 1=0.014), and grip strength (P 1  = 0.013) compared with the conservative group at the final follow-up. The change in volar angulation was an independent risk factor for the development of chronic DRUJ instability after conservative treatment for acute DRUJ instability. Conclusions For DRF combined with DRUJ instability, arthroscopic capsular suture repair to address TFCC tears was more effective at restoring DRUJ stability and yielded superior postoperative outcomes compared with conservative treatment of TFCC tears. The clinical efficacy of conservative DRF treatment in cases with acute DRUJ instability may deteriorate due to an increased change in volar angulation.